2017
DOI: 10.1007/s00216-017-0202-4
|View full text |Cite
|
Sign up to set email alerts
|

Impurity determination for hepcidin by liquid chromatography-high resolution and ion mobility mass spectrometry for the value assignment of candidate primary calibrators

Abstract: In metrology institutes, the state-of-the-art for purity analysis of peptides/proteins mainly addresses short and unfolded peptides. Important developments are anticipated for the characterization of nonlinear peptides or proteins. Hepcidin 1-25 is an interesting model system because this small protein contains four disulfide bridges with a particular connectivity that is difficult to reproduce and could induce a bias in quantification. Hepcidin 1-25 is involved in iron-related disorders and anemia, in an infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Ion mobility spectrometry (IMS) studies of two Hep-25 standards from two synthesis pathways showed different mobility profiles. Although the different mobilograms obtained were not further assigned, the authors suggested that multiple distinct conformers were present in these peptide standards [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Ion mobility spectrometry (IMS) studies of two Hep-25 standards from two synthesis pathways showed different mobility profiles. Although the different mobilograms obtained were not further assigned, the authors suggested that multiple distinct conformers were present in these peptide standards [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Commercially obtained synthetic hepcidin was used as candidate pRM (cpRM). Amino-acid analysis and comprehensive impurity analysis of the cpRM, performed by liquid chromatography high-resolution tandem MS, were performed for value assignment [13].…”
Section: Overview Study Designmentioning
confidence: 99%
“…Four or five mass fraction levels were selected to establish external calibration curves according to the impurity levels present in the AVP study material. The assigned mass fraction for an impurity detected by LC/HRMS is calculated by the equation given by Bros et al 19 …”
Section: Resultsmentioning
confidence: 99%